2004
DOI: 10.1007/s10600-005-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils of three species of Heracleum. Anticandidal activity

Abstract: Fruits of Heracleum crenatifolium Boiss., Heracleum sphondylium L. subsp. ternatum (Velen.) Brummitt, and Heracleum platytaenium Boiss. (Umbelliferae) were hydrodistilled to obtain essential oils that were then analyzed by GC and GC/MS. The major component was identified as octyl acetate (93.7, 87.6 and 31.6% respectively). Octyl butyrate was also characterized as the main component in H. platytaenium oil. Furthermore, anticandidal activity of the oils was evaluated using the microdilution broth method. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…The H. platytaenium extract had the greatest ovicidal effect in the single dose ovicidal test. A previous study on chemical components of H. platytaenium essential oil revealed that its essential oil contains isopropyl butyrate, octanal, heptyl acetate, hexyl butyrate, octyl acetate, (Z)-4-hexenyl butyrate, decanal, octanol, hexyl hexanoate and octyl butyrate (Iscan et al, 2004). Among these components, octyl acetate was the most abundant (Kürkçüoğlu et al, 1995) and is well known for being detrimental to insects (Carroll & Berenbaum, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The H. platytaenium extract had the greatest ovicidal effect in the single dose ovicidal test. A previous study on chemical components of H. platytaenium essential oil revealed that its essential oil contains isopropyl butyrate, octanal, heptyl acetate, hexyl butyrate, octyl acetate, (Z)-4-hexenyl butyrate, decanal, octanol, hexyl hexanoate and octyl butyrate (Iscan et al, 2004). Among these components, octyl acetate was the most abundant (Kürkçüoğlu et al, 1995) and is well known for being detrimental to insects (Carroll & Berenbaum, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…* Diameter of inhibition zones (mm) including diameter of sterile disk (6mm) (-), Inactive (7)(8)(9)(10)(11)(12)(13)(14), moderately active (>14), highly active…”
Section: Microorganismmentioning
confidence: 99%
“…To the best of our knowledge, although the essential oil composition of different members of Heracleum and their related antibacterial activity have been reported [13][14][15][16][17][18][19] , there have been no attempts to study the chemical composition and antimicrobial properties of the essential oils of flowers, seeds and stems of H. rechingeri which grows in Iran. Gas chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of our results with the literature showed that there is a considerable similarity among the essential oil of Z. absinthifolia and different species of Heracleum, such as H. crenatifolium Biss., H. platytaenium Boiss. and C. sphondylium L., whose fruit oils were comprised of octyl acetate as a characteristic component (Iscan, Ozek, Ozek, Duran, & Baser, 2004;Tosum et al, 2008). Hence, there is no chemotaxonomic significance in oil composition for the establishment of a distinction between Zosima and Heracleum genera.…”
Section: Natural Product Research 1127mentioning
confidence: 99%
“…It was shown to inhibit bacteria and fungi growth, with an MIC value of 400-500 mg mL À1 (Cseke et al, 2006;Iscan et al, 2004). Thus, the strong antimicrobial effects of Z. absinthifolia fruit oil could be primarily due to the presence of 1-octanol in the oil.…”
Section: Natural Product Research 1127mentioning
confidence: 99%